Information technology usage in the Islamic perspective: a systematic literature review - Al-Rahmi, Waleed Mugahed; Zeki, Akram M.; Alias, Norma; Saged, Ali Ali (Kamla-Raj Enterprises, 2017)
This paper involves a systematic and organized review of 155 research articles regarding Information Technology (IT) based on the Islamic perspective from 1992 to 2016. An analysis of studies dedicated to IT from the Islamic perspective was carried out on the basis of certain dimensions, namely, journal, country, author, year of publication, research methods, type of respondents, models, and theories. Based on the obtained findings, the use of quantitative and survey research methods (55.5%) dominate this field of study compared to qualitative research methods (23.9%) and mixed methods (20.7%). Furthermore, the findings have shown an increasing trend over recent years. However, to boost and enhance the IT continuance intention, it is important that future studies apply considerable use of theoretical and methodological approaches like the qualitative methods to examine the IT continuance intention based on the Islamic perspective.